Prognostic value of baroreflex sensitivity testing after acute myocardial infarction. Issue 2 (February 1992) - Farrell, T G; Odemuyiwa, O; Bashir, Y; Cripps, T R; Malik, M; Ward, D E; Camm, A J
Abstract : BACKGROUND--Disturbances of autonomic function are recognised in both the acute and convalescent phases of myocardial infarction. Recent studies have suggested that disordered autonomic function, particularly the loss of protective vagal reflexes, is associated with an increased incidence of arrhythmic deaths. The purpose of this study was to compare the value of differing prognostic indicators with measures of autonomic function and to assess the safety of arterial baroreflex testing early after infarction. METHODS--As part of a prospective trial of risk stratification in post-infarction patients arterial baroreflex sensitivity, heart rate variability, long term electrocardiographic recordings, exercise stress testing, and ejection fraction were recorded between days 7 and 10 in 122 patients with acute myocardial infarction. RESULTS--During a one year follow up period there were 10 arrhythmic events. Baroreflex sensitivity was appreciably reduced in these patients suffering arrhythmic events (1.73 SD (1.49) v 7.83 (4.5) ms/mm hg, 95% confidence interval (CI) 4.8 to 7.3, p = 0.0001). Significant correlations were noted with age (r = -0.68, p less than 0.001) but not left ventricular function. When baroreflex sensitivity was adjusted for the effects of age and ventricular function baroreflex sensitivity was still considerably reduced in the arrhythmic group (2.1 v 7.57 ms/mm Hg, p less than 0.0001). Depressed baroreflex sensitivity carried the highest relative risk for arrhythmic events (23.1, 95% CI 7.7 to 69.2) and was superior to other prognostic variables including left ventricular function (10.4, 95% CI 3.3 to 32.6) and heart rate variability (10.1, 95% CI 5.6 to 18.1). No major complications were noted with baroreflex testing and in particular no patients developed ischaemic or arrhythmic symptoms during the procedure. CONCLUSIONS--Disordered autonomic function as measured by depressed baroreflex sensitivity or reduced heart rate variability was associated with an increase incidence of arrhythmic events in post-infarction patients. Baroreflex testing can be safely performed in the immediate post-infarction period.